MIMIKRI, HIBRIDITAS, DAN AMBIVALENSI DALAM KUMPULAN CERPEN TEH DAN PENGKHIANAT KARYA IKSAKA BANU (KAJIAN POSKOLONIALISME) - Wardianto, Bayu Suta (Balai Bahasa Sumatra Barat, 2021)
Literary works are born from the results of one's thoughts or expressions, literary works grow and develop according to the situation or condition of the author. In addition to being used as a medium of entertainment, literary works are also useful as learning, critical, and documentation of historical events that have occurred in its time. This form of research is descriptive qualitative that uses content analysis strategy. The source of this research data was obtained from a collection of short stories Tea and Traitors by Iksaka Banu. The data was obtained from the results of the study and analysis of the collection of short stories Tea and Traitors by Iksaka Banu. The selected data is classified according to the concepts of mimicry, ambival, hybridity. Testing the validity of the data in this study echoes the trianggulasi theory. The data analysis techniques used are the interactive techniques of milles and huberman models. The results of this study found several forms of mimicry. A form of mimicry that is performed by minorities against the dominant. In the impersonation of hybridity aspects of the short story collection Tea and Traitors found a form of impersonation of lifestyle. The form of ambivalence in the short story collection Tea and Traitors found several forms of ambivalence, such as modeling or dress and racism by the dominant against minorities. Postlonial studies of tea and traitor short stories can be used as material for studying literature in schools because they contain moral values.